2018
DOI: 10.1177/2051415818817127
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tadalafil against lower urinary tract symptoms after low-dose-rate brachytherapy in prostate cancer patients

Abstract: This study was performed to evaluate the effects of addition of tadalafil to tamsulosin in the treatment of brachytherapy patients with lower urinary tract symptoms (LUTS). Methods: Localized prostate cancer patients who developed LUTS after low-dose-rate brachytherapy (LDR-BT) were first treated with alpha-1 blockers (tamsulosin, 0.2 mg per day). Those still suffering from LUTS were additionally treated with phosphodiesterase type 5 inhibitor (tadalafil, 5 mg/day). LUTS was evaluated by the International Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…However, the effect of PDE5 inhibitor treatment alone was not evaluated in the report. We previously reported that tadalafil add‐on to tamsulosin is effective in attenuating LUTS after LDR as a preliminary study for this trial 11 . In this trial, we confirmed the efficacy of tadalafil, compared with tamsulosin, on LUTS after LDR.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…However, the effect of PDE5 inhibitor treatment alone was not evaluated in the report. We previously reported that tadalafil add‐on to tamsulosin is effective in attenuating LUTS after LDR as a preliminary study for this trial 11 . In this trial, we confirmed the efficacy of tadalafil, compared with tamsulosin, on LUTS after LDR.…”
Section: Discussionsupporting
confidence: 74%
“…We previously reported that tadalafil add-on to tamsulosin is effective in attenuating LUTS after LDR as a preliminary study for this trial. 11 In this trial, we confirmed the efficacy of tadalafil, compared with tamsulosin, on LUTS after LDR. ED is also one of the problems affecting QoL after LDR for localized prostate cancer.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations